Identification of a novel major QTL and F-box candidate genes controlling seed dormancy in common wheat - Yuxia Lyu; Yaoyao Zhao; Wenbo Lu; Xu Pan; Wei Gao; Litian Zhang; Huanfeng Wang; Zhaoyu Yu; Ruihan Wang; Tingfeng Shou; Bingbing Tian; Jiajia Cao; et al. (Theoretical and Applied Genetics, 2026)

Emergence of anthropogenic warming in Antarctica - Zihuan Zhang; Sai Wang; Deliang Chen; Tingfeng Dou; Cunde Xiao; Annette Rinke; Shoudong Zhao; Petra Heil; Wen Chen; Minghu Ding (Science Bulletin, 2026)

Unveiling the synergistic mechanism of lipid oxidation and protein glycosylation in the formation of advanced glycation end products in tilapia during thermal processing - Lijia Yang; Hanyao Liu; Penglong Liu; Tingfeng Zhang; Weifeng Liu; Yehui Zhang; Wangdong Li; Yang Liu; Tiantian Zhao (Food Research International, 2026)

Electrochemical oxidation of caprolactam wastewater by a SnO2-Sb electrode with reduced TiO2-xN interlayer:Electrode characterization, environmental impact factors and degradation pathways - Tingfeng Wang; Jun Ma; Zhiqiang Sun; Fang Chang; Zhendong Li; Yingjie Zhao; Wei Ye; Huiting Li (Environmental Research, 2026)

Uranium release from iron-rich acid soils under IPCC elevated CO2 scenarios: One-sided organic nanocolloidal dominance rather than expected iron oxide colloids - Ziyan Wang; Tingfeng Cheng; Caiqin Wang; Yuwei Zhao; Daoyong Zhang; Xiangliang Pan (Journal of Hazardous Materials, 2025)

A novel scene coupling semantic mask network for remote sensing image segmentation - Xiaowen Ma; Rongrong Lian; Zhenkai Wu; Renxiang Guan; Tingfeng Hong; Mengjiao Zhao; Mengting Ma; Jiangtao Nie; Zhenhong Du; Siyang Song; Wei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Enhancement of electrocaloric strength by grain configuration design - Cuiping Xu; Xiaofan Sun; Peiqi Ji; Min Zhao; Tingfeng Li; Peng Chen; Hong-Ling Cai; X.S. Wu (Chemical Engineering Journal, 2025)

Inhibition of STRA6 suppresses NSCLC growth via blocking STAT3/SREBP-1c axis-mediated lipogenesis - Yue Zhou; Rong Zhou; Ning Wang; Tingfeng Zhao; Pan Qiu; Chenzi Gao; Meijia Chang; Ning Lin; Xu Zhang; John Zhong Li; Qian Wang (Molecular and Cellular Biochemistry, 2025)

Two-stage bidirectional coevolutionary algorithm for constrained multi-objective optimization - Shulin Zhao; Xingxing Hao; Li Chen; Tingfeng Yu; Xingyu Li; Wei Liu (Swarm and Evolutionary Computation, 2025)

Fast and Deterministic Underwater Point Cloud Registration for Multibeam Echo Sounder Data - Liang Zhao; Lan Cheng; Tingfeng Tan; Chun Cao; Feihu Zhang (Journal of Marine Science and Engineering, 2024)
Investigating underwater environments using Multi-Beam Echo Sounder (MBES) point cloud registration technology is a critical yet underdeveloped area in oceanographic research. This paper presents a fast, deterministic Branch-and-Bound (BnB) method with four degrees of freedom, which combines Inertial Measurement Unit (IMU) data with MBES point cloud data for precise registration. Given the prevalence of outliers and noise in underwater acoustic measurements, the BnB method is employed to provide globally deterministic solutions. However, due to the exponential convergence speed of the BnB method with respect to the dimensionality of the solution space, searching within a six-degree-of-freedom parameter space (three rotational and three translational degrees of freedom) can be extremely time-consuming. To this end, the Z-axis of the point cloud is aligned with the gravitational direction of the IMU, reducing the rotational degrees of freedom from three to one, specifically concerning yaw. Additionally, an outlier exclusion strategy is introduced to eliminate mismatches, significantly reducing the number of key-point correspondences and thereby improving registration efficiency. Experiments conducted on both public and real-world lake datasets demonstrate that the proposed method achieves a favorable balance between speed and accuracy, outperforming other tested methods and meeting the demands of contemporary research.

Engineering microalgae for robust glycolate biosynthesis: Targeted knockout of hydroxypyruvate reductase 1 combined with optimized culture conditions enhance glycolate production in Chlamydomonas reinhardtii - Suihao Yan; Yuyong Hou; Meijie Cui; Tingfeng Cheng; Sihan Lu; Zhiyong Liu; Bicheng Deng; Weijia Liu; Menglin Shi; Liangcai Lin; Longjiang Yu; Lei Zhao (Bioresource Technology, 2024)

Underwater Gyros Denoising Net (UGDN): A Learning-Based Gyros Denoising Method for Underwater Navigation - Chun Cao; Can Wang; Shaoping Zhao; Tingfeng Tan; Liang Zhao; Feihu Zhang (Journal of Marine Science and Engineering, 2024)
Autonomous Underwater Vehicles (AUVs) are widely used for hydrological monitoring, underwater exploration, and geological surveys. However, AUVs face limitations in underwater navigation due to the high costs associated with Strapdown Inertial Navigation System (SINS) and Doppler Velocity Log (DVL), hindering the development of low-cost vehicles. Micro Electro Mechanical System Inertial Measurement Units (MEMS IMUs) are widely used in industry due to their low cost and can output acceleration and angular velocity, making them suitable as an Attitude Heading Reference System (AHRS) for low-cost vehicles. However, poorly calibrated MEMS IMUs provide an inaccurate angular velocity, leading to rapid drift in orientation. In underwater environments where AUVs cannot use GPS for position correction, this drift can have severe consequences. To address this issue, this paper proposes Underwater Gyros Denoising Net (UGDN), a method based on dilated convolutions and LSTM that learns and extracts the spatiotemporal features of IMU sequences to dynamically compensate for the gyroscope’s angular velocity measurements, reducing attitude and heading errors. In the experimental section of this paper, we deployed this method on a dataset collected from field trials and achieved significant results. The experimental results show that the accuracy of MEMS IMU data denoised by UGDN approaches that of fiber-optic SINS, and when integrated with DVL, it can serve as a low-cost underwater navigation solution.

Underwater Mapping and Optimization Based on Multibeam Echo Sounders - Feihu Zhang; Tingfeng Tan; Xujia Hou; Liang Zhao; Chun Cao; Zewen Wang (Journal of Marine Science and Engineering, 2024)
Multibeam echo sounders (MBESs) enable extensive underwater environment exploration. However, due to weak correlation between adjacent multibeam sonar data and difficulties in inter-frame feature matching, the resulting underwater mapping accuracy frequently falls short of the desired level. To address this issue, this study presents the development of a multibeam data processing system, which includes functionalities for sonar parameter configuration, data storage, and point cloud conversion. Subsequently, an Iterative Extended Kalman Filter (iEKF) algorithm is employed for odometry estimation, facilitating the initial construction of the point cloud map. To further enhance mapping accuracy, we utilize the Generalized Iterative Closest Point (GICP) algorithm for point cloud registration, effectively merging point cloud data collected at different times from the same location. Finally, real-world lake experiments demonstrate that our method achieves an Absolute Trajectory Error (ATE) of 15.10 m and an average local point cloud registration error of 0.97 m. Furthermore, we conduct measurements on various types of artificial targets. The experimental results indicate that the average location error of the targets calculated by our method is 4.62 m, which meets the accuracy requirements for underwater target exploration.

Photo-thermochromic W18O49/hydrogel hybrid smart windows for graded and dual-band sunlight control - Jiahui Tao; Shouqin Tian; Bin Li; Tingfeng Ma; Longxiao Zhou; Xiujian Zhao (Chemical Engineering Journal, 2024)

Reversible photochromic W18O49: Mechanism revealing and performance improvement for smart windows - Tingfeng Ma; Bin Li; Shouqin Tian; Jiachen Qian; Longxiao Zhou; Qiufen Liu; Baoshun Liu; Xiujian Zhao; Gopinathan Sankar (Chemical Engineering Journal, 2023)

Association of blood mercury levels with bone mineral density in adolescents aged 12–19 - Ke Xu; Bingqian Gao; Tingfeng Liu; Jiayi Li; Yixin Xiang; Yicheng Fu; Mingyi Zhao (Environmental Science and Pollution Research, 2023)

Exploring and quantifying the relationship between instantaneous wind speed and turbidity in a large shallow lake: case study of Lake Taihu in China - Wenhao Ding; Jinxiao Zhao; Boqiang Qin; Tingfeng Wu; Senlin Zhu; Yun Li; Shikai Xu; Shiping Ruan; Yong Wang (Environmental Science and Pollution Research, 2021)